Accelerated two-stage bioprocess for hydrogen and methane production from palm oil mill effluent using continuous stirred tank reactor and microbial electrolysis cell - Krishnan, Santhana; Mohd Fadhil, Md Din; Shazwin, Mat Taib; Mohd Nasrullah, Zulkifli; Mimi Sakinah, A. M.; Zularisam, A. W.; Kamyab, Hesam; Chelliapan, Shreeshivasan; Rezania, Shahabaldin; Singh, Lakhveer (Elsevier, 2019)
This paper investigates the production of hydrogen (H2) and methane (CH4) from palm oil mill effluent (POME) using an integrated approach of thermophilic continuous stirred tank reactor (CSTR) and mesophilic microbial electrolysis cell (MECs). CSTR reactor was operated at pH 5.5, 80 rpm, 2 days HRT, 60 g COD L-1 d-1 organic loading rate (OLR) and 55 °C temperature with the given hydrogen yield of 205 ml H2 gCOD-1along with acetic, butyric, propionic, and lactic acid as by-products. Continuous, single-chambered MECs fed with dark fermentation effluents were operated at an applied voltage of 0.5 V at 37 °C to obtain methane yield and production rate (MPR) of 290 ml CH4 gCOD-1 and 2700 ml CH4 L-1 at 8 days of hydraulic retention times (HRT). The overall process led to total energy recovery of 92.72% with 91% COD removal efficiency. Microbial community analysis reveals Thermoanerobacterium sp dominated in CSTR whereas exoelectrogens of Methanobacterium formicicum and Methanobacterium beijingense were found to be the chief dominant microbial species on anodic electrode of MECs.